Smart City North: economic and labour force impacts of call centres in Sudbury, Ontario. (1st July 2007) - ,; ,
Abstract : Geographers debate the value of telecommunications-mediated jobs (or ''eWork'') for the economies of smaller, deindustrialised and rural areas. Against the backdrop of globalisation, various regions across Canada are courting knowledge-sector business development. Sudbury, a medium-sized northern Ontario city, has invested heavily in telecommunications infrastructure and touted its assets and resources to potential employers in order to help its ailing economy. Since the late 1990s, Sudbury has attracted some ten new call centres, with a combined labour force numbering about 4, 000. In this article, we use Sudbury as a case study to consider the overall effects of eWork on a local labour force and a regional economy. From the combined perspectives of employers, unions, municipal planners, local economic development officials, and academic researchers, we assess the net impact of these new economy jobs.